How to Coordinate Urban Ecological Networks and Street Green Space Construction? Insights from a Multi-Scale Perspective - Shujun Hou; Ying Yu; Taeyeol Jung; Xin Han (Land)
Rapid socio-economic development and imbalanced ecosystem conservation have heightened the risk of species extinction, reduced urban climate adaptability, and threatened human health and well-being. Constructing ecological green space networks is an effective strategy for maintaining urban ecological security. However, most studies have primarily addressed biodiversity needs, with limited focus on coordinating street spaces in human settlement planning. This study examines the area within Chengdu’s Third Ring Road, employing the following methodologies: (1) constructing the regional ecological network using Morphological Spatial Pattern Analysis (MSPA), the Integrated Valuation of Ecosystem Services and Trade-offs (InVEST) model, and circuit theory; (2) analyzing the street green view index (GVI) through machine learning semantic segmentation techniques; and (3) identifying key areas for the coordinated development of urban ecological networks and street green spaces using bivariate spatial correlation analysis. The results showed that (1) Chengdu’s Third Ring Road exhibits high ecological landscape fragmentation, with 41 key ecological sources and 94 corridors identified. Ecological pinch points were located near urban rivers and surrounding woodlands, while ecological barrier points were concentrated in areas with dense buildings and complex transportation networks. (2) Higher street GVI values were observed around university campuses, urban parks, and river-adjacent streets, while lower GVI values were found near commercial areas and transportation hubs. (3) To coordinate the construction of ecological networks and street green spaces, the central area of the First Ring Road and the northwestern region of the Second and Third Ring Roads were identified as priority restoration areas, while the northern, western, and southeastern areas of the Second and Third Ring Roads were designated as priority protection areas. This study adopts a multi-scale spatial perspective to identify priority areas for protection and restoration, aiming to coordinate the construction of urban ecological networks and street green spaces and provide new insights for advancing ecological civilization in high-density urban areas.